2008
DOI: 10.1111/j.1476-4431.2008.00349.x
|View full text |Cite|
|
Sign up to set email alerts
|

Association of hyperlactatemia with age, diagnosis, and survival in equine neonates

Abstract: Objective – To investigate the association between blood lactate concentration, measured at admission and following 12–36 hours of treatment, and age, diagnosis, and survival in neonatal foals. Design – Retrospective, observational study. Setting – Two equine referral hospitals. Animals – One hundred and twelve foals ≤96 hours of age were included. Interventions – Arterial or venous blood samples were obtained from all foals at admission and surviving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
65
2
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(73 citation statements)
references
References 22 publications
5
65
2
1
Order By: Relevance
“…Moreover, in two severe diseases, large intestinal strangulating disease and colitis, both [LAC] and [LAC]Δ T appeared to have the strongest associations with outcome. Blood lactate concentration has long been recognized as a useful indicator of disease severity in human medicine 1–3 and there is increasing interest in its value in veterinary medicine as a resuscitation end‐point and prognostic indicator 4–9 . However, as with any variable, measurement of [LAC] at a single time point can be misleading and admission [LAC] is not always strongly associated with outcome 10–13 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, in two severe diseases, large intestinal strangulating disease and colitis, both [LAC] and [LAC]Δ T appeared to have the strongest associations with outcome. Blood lactate concentration has long been recognized as a useful indicator of disease severity in human medicine 1–3 and there is increasing interest in its value in veterinary medicine as a resuscitation end‐point and prognostic indicator 4–9 . However, as with any variable, measurement of [LAC] at a single time point can be misleading and admission [LAC] is not always strongly associated with outcome 10–13 .…”
Section: Discussionmentioning
confidence: 99%
“…Studies in equine neonates have shown that [LAC] remains increased in nonsurvivors 4,5 and a recent retrospective study demonstrated an association between the change in [LAC] over time ([LAC]Δ T ), used as a rough estimate of lactate clearance, and survival 6 . In a recent study of neonatal foals, [LAC]Δ T was lower (ie, [LAC] decreased more slowly) in nonsurvivors when compared with survivors, similar to what has been observed in adult humans 6,17,19 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hyperlactatemia has been used as a prognostic guide in ill neonatal foals, with blood lactate concentration significantly higher in nonsurviving foals. [34][35][36] Hyperlactatemia can occur via a multitude of pathophysiologic mechanisms, with the most common mechanism arising from anaerobic tissue metabolism, which occurs with an imbalance between oxygen delivery and tissue demand (type A hyperlactatemia). 37 Hyperlactatemia may also occur under conditions of adequate oxygen delivery (type B hyperlactatemia) in the face of increased or impaired oxygen utilization secondary to the systemic inflammatory response syndrome, sepsis, neoplasia, or mitochondrial dysfunction.…”
Section: 33mentioning
confidence: 99%
“…Hypo-oder Hyperglykämie (Hollis et al 2008) und Hyperlaktatämie (Corley et al 2005, Henderson et al 2008, Veronessi et al 2009, Wotman et al 2009) sowie eine gestörte Laktatclearance (Wotman et al 2009) wurden bei erkrankten Fohlen als Indikatoren einer ungünstigen Prognose beschrieben. Eine erhöhte Anionenlücke korrelierte bei Fohlen mit respiratorischen Erkrankungen und bei Fohlen in intensivmedizinischer Therapie mit schlechteren Überlebenschancen (Hoffman et al 1992, Bedenice et al 2003b).…”
unclassified